Neoclassical growth and the natural resource curse puzzle - Guilló, María Dolores; Pérez-Sebastián, Fidel (Journal of international economics, 2015)
We advance a novel mechanism that helps to explain the puzzling evidence on the natural resource curse. The new channel arises in a standard dynamic Heckscher-Ohlin model composed of small-open economies that take international output prices as given. Within this framework, a more capital-intensive primary sector implies that natural-resource abundant economies grow more slowly along the adjustment path. This effect might be only temporary because the natural input also affects long-run income, and not necessarily in the same direction as transitional growth. We produce quantitative results that show that the new mechanism can account for a significant fraction of the observed output growth gap between resource rich and resource poor U.S. states.
Keywords: Natural resource curse; Economic growth; Dynamic Heckscher–Ohlin; Factor shares; Small open economy